(untitled) (International Journal of Engineering and Computer Science, 2018)
Software Testing is a process of detecting errors while executing a program so that we get a zero defect software. The aim of this paper is to evaluate and establish a comprehensive view of the field of software testing. The main objective of this paper is to bring out the relevant issues of the mobile application testing and the tools to remove them. There are many tools available in the market at the moment, each having its own features to test software. For this paper, we have discussed a set of tools, which are constructed to tackle the appropriate topic problems. Software testing is a crucial area of research and a lot of development has been made. We did not mean to give a complete overview of the mobile application testing field- challenges and methodologies, rather we intended to show an overview of the tools which are meant to overcome the challenges of the software testing.